Multi-channel pricing strategies for pharmaceutical supply chains considering channel power and price competition - Yan Wen; Yan Wei; Xiyuan Yu (PLoS ONE, 2025)
In the context of the reality that pharmaceutical manufacturers and retailers are simultaneously opening online sales channels, three different multi-channel pharmaceutical supply chain game models were constructed based on game theory, considering channel power, triple price competition among channels, and health insurance reimbursement policies, among others, comparing and analyzing the effects of each influencing factor on pharmaceutical pricing and profits in the pharmaceutical supply chain. It was found that inter-channel price competition did not always reduce the prices of a retailer’s pharmaceuticals; price competition between physical retail channels and online retail channels could lead to higher pharmaceutical prices, but direct sales channels effectively reduced pharmaceutical prices. Furthermore, as the channel power of pharmaceutical retailers strengthens, retail prices will increase, and retailers’ profits will rise. However, as the channel power of pharmaceutical manufacturers increases, their profits will grow, but retail prices will correspondingly decrease. Appropriate increasing in the health insurance reimbursement rate could improve pharmaceutical pricing in each channel and the total profits of the pharmaceutical supply chains.